Determining the performance of public sector organizations: An analysis of competence, motivation, career paths, and compensation through job satisfaction - Sismiati, Sismiati; Susanto, Primadi Candra; Gunawan, Aang; Fahriza, Basri (Annals of Human Resource Management Research, 2025)
Purpose: The purpose of this study is to examine the influence of competence, motivation, career path, competence, and job satisfaction on organizational performance in public sector companies in Indonesia. Methodology: This study employs a descriptive qualitative approach using a comparative literature review method. Data were collected from previous relevant studies obtained through reputable academic databases, including Thomson Reuters, Springer, Taylor & Francis, Scopus, Emerald, Elsevier, Sage, Web of Science, Sinta 2–5 Journals, DOAJ, EBSCO, Google Scholar, Copernicus, and digital reference books to analyze relationships among key variables. Results: The findings indicate that competence, motivation, career path, and compensation each positively influence job satisfaction and organizational performance. Job satisfaction also directly enhances organizational performance. Furthermore, competence, motivation, career path, and compensation indirectly affect organizational performance through the mediating role of job satisfaction. Conclusions: Competence, motivation, career path, and compensation significantly enhance job satisfaction and organizational performance in Indonesia’s public sector. Limitations: This study is limited to Organizational Performance and Job Satisfaction in the public sector in Indonesia. Contribution: This study examines how competence, motivation, career path, compensation, and job satisfaction influence public sector organizational performance.